The Paradigm of Inter-Agency Partnership in the Modern Quantum World: The International Security Sector - Лісовський, П.; Лісовська, Ю. (Навчально-науковий інститут міжнародних відносин КНУ імені Тараса Шевченка, 2019)
The article considers the modern transitional model of inter-agency partnership as a qualitatively new semantic state of person, state and society, in which the international security sector plays an important role. On the basis of the analysis, a new transient model of inter-agency partnership in the modern quantum world has been outlined that includes a set of original (natural, authentic, exclusive, etc.) phenomen, in which the quantum is the minimum unit of any physical object that has corpuscular-wave universe structure in the modern geopolitics of states. At the same time, the quantum world is a collection of original phenomen, investigated by a phenomenal approach. The author's vision regarding the innovative updating of the content of anti-corruption education on the European level is revealed. No less strategic direction of interdepartmental partnership is cyber justice - the introduction of new practices from both the developers of new technologies and users of such technologies, which collectively provide the quality of services provided by the courts. The conceptual model of quantum philosophy as an entropy matrix in interdepartmental partnership is highlighted. The investment policy of states in the quantum world is outlined. It has been argued that the state border guard is the key to success in the international legal field of interdepartmental partnership characterized by a qualitatively new semantic state of the individual, state and society, in which the international security sector plays an important role. It is alleged that security sector reform in the inter-agency partnership of the world contributes to the qualitative growth of the scientific and technological potential as a breakthrough in the future. Under current circumstances, anti-corruption education is an important criterion in the international security sector as an intellectual critical infrastructure of inter-agency partnership. It is proved that the innovative updating of the content of education at the European level today should be the aggregate fundamental matrix of interagency, providing the corresponding quality on the basis of prestige, competitiveness and perspective needs of the individual, state and society. The filling of interdepartmental partnership with specific content takes place depending on the specific goals and tasks that are solved by it.

У статті розглянута сучасна перехідна модель міжвідомчого партнерства як якісно новий семантичний стан особи, держави та суспільства, в якому міжнародний сектор безпеки відіграє актуальну роль. При цьому квантовий світ – це сукупність оригінальних явищ, досліджених феноменальним підходом. Розкрито авторське бачення стосовно інноваційного оновлення змісту антикорупційної освіти на європейському рівні. Не менш стратегічним напрямком міжвідомчого партнерства є кіберправосуддя –впровадження нових практик як з боку розробників нових технологій, так і з боку користувачів таких технологій, що сукупно забезпечують якість послуг, які надаються судами. Висвітлено концептуальну модель квантової філософії як ентропійної матриці в міжвідомчому партнерстві. У цьому змісті визначено, що квант – це мінімальна одиниця будь-якого фізичного об’єкта, яка має корпускулярно-хвильову вселенську структуру у сучасній геополітиці держав. Окреслена інвестиційна політика держав у квантовому світі. Стверджено, що саме охорона державного кордону є запорукою успіху в міжнародно-правовому полі міжвідомчого партнерства, яке характеризується якісно новим семантичним станом особи, держави та суспільства, в якому міжнародний сектор безпеки відіграє актуальну роль. За існуючих обставин, у міжнародному секторі безпеки важливим критерієм виступає антикорупційна освіта як інтелектуальна критична інфраструктура міжвідомчого партнерства.
Парадигма міжвідомчого партнерства у сучасному квантовому світі: міжнародний сектор безпеки
Keywords: парадигма; міжвідомче партнерство; кіберправосуддя; квант; безпека; політика; paradigm; interdepartmental partnership; cyber justice; quantum; security; politics